PENGARUH VARIASI LATIHAN PASSING TERHADAP KEMAMPUAN PASSING BAWAH BOLA VOLI PADA ATLET CLUB AKRAL DELI SERDANG TAHUN 2023 (JURNAL ILMU KEOLAHRAGAAN, 2024)
This study aims to determine the effect of variations in passing training on volleyball underpassing abilities in Akral Deli Serdang club athletes in 2023. This research is experimental research which refers to pre-test, treatment and post-test. The population of this study was all athletes from Club Akral Deli Serdang, totaling 50 people. Sampling used purposive sampling technique, the research sample consisted of 10 people. This research was carried out for 6 weeks, namely in 18 meetings with a training frequency of 3 times a week. The test instrument used is Passing Below Sampek. Hypothetical analysis, namely, the effect of variations in passing training on the volleyball underpassing ability of Akral Deli Serdang club athletes in 2023, obtained by hypothesis testing t_(count) of 9.73. Next, this price is compared with t_(table) with dk = n-1 = 10-1 at the real level ï¡ = 0.05 = 2.26. In the hypothesis testing criteria it is stated that at t_count >t_table= 9.73 > 2.26 with ï¡ = 0.05 then H_(0) is rejected and H_a is accepted. In this case, it can be concluded that the lower passing training has had a significant influence on the lower passing of volleyball athletes at Akral Deli Serdang Club in 2023
Keywords: Variations of lower passing exercises with letter models